Using Student-Produced Videos to Communicate about Science - Ricky W Telg; Kathryn Stofer; Rachel DeConna (Journal of Applied Communications, 2018)
This professional development article provides a case study of the Explore Research at the University of Florida video project, conducted by University of Florida undergraduate and graduate students. Students take an advanced digital media production course where they develop videos documenting research at the university. The videos are then displayed at the Museum of Natural History and various online, broadcast, and cable television outlets. This article also provides suggestions for individuals who may want to develop their own partnerships with similar organizations in their courses.
Keywords: museum; video; course